Nickel-Catalyzed Enantioselective Reductive Spirocyclization of 1,6-Enynes with o-Bromobenzaldehydes - Guo, Haoyun; Chen, Yate; Kong, Wangqing (Synthesis, 2024)
We developed a Ni-catalyzed asymmetric reductive spirocyclization of 1,6-enynes with o-haloaryl aldehydes. This approach provides an efficient method for the construction of chiral spiroindanone pyrrolidine derivatives in good yields with excellent enantio- and diastereoselectivity (up to 99% ee, >20:1 dr). This reaction does not require pre-prepared organometallic reagents and exhibits excellent substrate compatibility.
Keywords: nickel catalysis; enantioselectivity; reductive spirocyclization; 1,6-enynes; spiroindanones